2020
DOI: 10.3390/math8081254
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Robot Wall-Following Control Using Fuzzy Logic Controller with Improved Differential Search and Reinforcement Learning

Abstract: In this study, a fuzzy logic controller with the reinforcement improved differential search algorithm (FLC_R-IDS) is proposed for solving a mobile robot wall-following control problem. This study uses the reward and punishment mechanisms of reinforcement learning to train the mobile robot wall-following control. The proposed improved differential search algorithm uses parameter adaptation to adjust the control parameters. To improve the exploration of the algorithm, a change in the number of superorganisms is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 29 publications
(48 reference statements)
0
12
0
Order By: Relevance
“…Finally, the automatic navigation and obstacle avoidance capabilities of robots in unknown environments were verified for achieving the objective of mobile robot control. Relative to our previous published papers [24][25][26], the major contributions of this study are as follows: (1) an efficient KNFC is proposed for mobile robot navigation control, (2) the proposed KCMDE algorithm contains features of both the CA and DE strategy, and is implemented using the knowledge sources of the belief space in the CA to increase global search ability, and (3) in special environments, two thresholds are used to switch the controller mode between the wall-following mode and the general controller.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations
“…Finally, the automatic navigation and obstacle avoidance capabilities of robots in unknown environments were verified for achieving the objective of mobile robot control. Relative to our previous published papers [24][25][26], the major contributions of this study are as follows: (1) an efficient KNFC is proposed for mobile robot navigation control, (2) the proposed KCMDE algorithm contains features of both the CA and DE strategy, and is implemented using the knowledge sources of the belief space in the CA to increase global search ability, and (3) in special environments, two thresholds are used to switch the controller mode between the wall-following mode and the general controller.…”
Section: Introductionmentioning
confidence: 91%
“…This section introduces the experiments conducted using the mobile robot PIONEER 3-DX [24][25][26] (see Figure 1). The robot includes eight front ultrasonic sensors, a battery, two differential drive wheels, and wheel encoders.…”
Section: Description Of the Mobile Robot Structure And Sensor Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuzzy logic control (FLC) is a structure that mimics human knowledge or action based on linguistic rules that are tuned according to the designer [28][29][30]; these type of controllers have been used in applications for maximum power point tracking, such as fuel cells and photo-voltaic systems [31,32], electrical drivers [33], etc. The author of [34] indicated that FLC that is based on PID grants a high accuracy for PEAs guidancem, but it can also provide other advantages over alternative control structures.…”
Section: Introductionmentioning
confidence: 99%